Large Inter-individual Variation in Postprandial Lipemia Following a Mixed Meal in over 1000 Twins and Singletons from the UK and US: The PREDICT I Study (OR19-06-19). (13th June 2019) - Berry, Sarah; Valdes, Ana; Davies, Richard; Khatib, Haya Al; Delahanty, Linda; Drew, David; Chan, Andrew Tan; Segata, Nicola; Franks, Paul; Spector, Tim
Abstract: Objectives: Postprandial lipemia is an important risk factor for cardiovascular disease, independent of fasting levels, and is influenced by multiple factors including; environmental, genetic, metabolic, metagenomic and the meal-context. Postprandial lipemic responses may therefore differ between individuals, however previously this has only been studied in limited numbers. The PREDICT I study is the largest study to date to measure inter-individual variability in postprandial lipemic responses using a standardized test meal model. Methods: A multi-center postprandial study of 1000 individuals from the UK (unrelated, identical and non-identical twins) and 100 unrelated individuals from US, assessed postprandial (hourly 0–6h) lipemic responses to sequential mixed-nutrient dietary challenges (50g fat and 85g carbohydrate at 0h; 22g fat and 71g carbohydrate at 4h) in a clinical setting. Inter-individual variability in postprandial triacylglycerol (TG) responses was measured for incremental area under the curve (iAUC), Cmax, Tmax and increase above fasting at 5h (mean peak concentration time-point). Results: Analysis showed high inter-individual variability in postprandial lipemic responses (Figures 1–3) in the tightly controlled clinic setting (interim analysis of n = 537); IQR (median) was; iAUC (0-6h) 2.34 (2.38) mmol/L.h; Cmax 1.32 (2.02) mmol/L; Tmax 30.0 (300) min; and increase above fasting at 5h 0.92 (0.95). TG variation was higher in the non-fasting versus the fasting state; fasting TG concentration IQR (median); 0.57 (0.91) mmol/L. Conclusions: The large variation in the magnitude and pattern of lipemic responses to identical meals in healthy people demonstrates the limitations of using the group mean and the importance of individualized dietary approaches. Ongoing exploration in PREDICT I of the determinants of postprandial lipemic responses considering environmental, genetic, metagenomic and microbiome variables will significantly advance our ability to predict an individual's postprandial response. Funding Sources: NIHR, Wellcome Trust, Zoe Global Ltd. Supporting Tables, Images and/or Graphs: